Undesirable stressful life events, impact, and correlates during midlife: observations from the Seattle midlife women's health study - Annette Joan Thomas; Ellen Sullivan Mitchell; Nancy Fugate Woods (BMC, 2019)
Abstract Purpose To examine the undesirable stressful life events midlife women experience, including: 1) which life events midlife women reported most frequently; 2) which life events women rated as most undesirable; and 3) whether age, years of education, income, employment, race/ethnicity, marital status, being a parent, and the menopausal transition stage were associated with the impact scores of the life event categories. Background In addition to the menopausal transition, midlife is a time of increased responsibilities for women related to multiple roles such as taking care of children, caring for elderly parents, managing households, and working outside the home. These multiple roles put midlife women at risk for increased stress with little time for themselves in order to relieve stress. Methods The sample used in this study is part of a larger longitudinal study, The Seattle Midlife Women's Health Study. Women (N = 380 for Occasion 1) completed the 77-item Life Events Scale on four occasions during the course of the SMWHS: Occasion 1 (1990), Occasion 2 (1992), Occasion 3 (1997), and Occasion 4 (2000). In addition to descriptive analyses of frequency of life events and the undesirable impact of life events, demographic correlates (age, education, income, employment, being a parent as well as marital status, race/ethnicity, and menopausal transition stages) were examined in relation to the stressful life event scores. Results Highest scores of undesirable life events were for categories of both Financial and Family/Friends over 3 of the 4 occasions. Health and Crime/Legal scores were among the highest for 2 occasions. Impact of the undesirable stressful life events was greatest for categories of Family/Friends; Personal/Social; Work; and, Health. Age, income, marital status, being a parent, and menopausal transition stage were each associated with specific categories of the stressful event impact scores. Conclusion Most commonly reported undesirable life events were not those women described as having the greatest impact. Impact of life event stress reflected women's social roles and connections as seen in the categories with the highest impact scores: Family/Close Friends, Personal/Social, and Work. Menopausal transition stages were related only to undesirable health events.